Pengaruh Budaya Organisasi, Kompensasi, Motivasi Dan Stress Kerja Terhadap Kinerja Pegawai KPP Pratama Kediri - Dahniar Kusumastuti; Abu Talkah; Nisa Mutiara (Otonomi, 2023)
Every company expects its employees to perform well. This study aims to analyze the influence of organizational culture, compensation, motivation, and work stress together on the performance of Employees of Kantor Pajak Pelayanan Kediri. This type of research is quantitative. Free variables (X) of organizational culture, compensation, motivation, and work stress and bonded variables (Y) of employee performance are used as research objects. The research instrument uses questionnaire questionnaires. Data analysis techniques include instrument trials, descriptive analysis, classical assumption tests, multiple linear regressions, and hypothesis tests. Research results: (1) Organizational Culture has a significant effect on employee performance at Kantor Pelayanan Pajak Kediri. (2) Work compensation has a significant effect on employee performance at Kantor Pelayanan Pajak Kediri. (3) Work motivation has a significant impact on employee performance at Kantor Pelayanan Pajak Kediri. (4) Work stress has no significant effect on employee performance at Kantor Pelayanan Pajak Kediri.